(untitled) (Educational Dimension, 2021)
The paper discusses AR/VR/MR/XR technologies in learning namely their influence/ opportunity and risks’ mitigation. Main aspects are as follows: methodology (factors influencing a student’s cybersickness in AR/VR/MR/XR, the improved model of the cognitive activity in synthetic learning environment). It has been developed the technique and ICT to study psychophysiological changes in normal and stressed conditions. The experimentation results demonstrated that decrease in myocardial tension index under cognitive performance conditions in immersive activity over time of observation was more significant and this fact could be accounted in measurement of influence of the synthetic environment on students, as well as the technique to measure AR/VR/MR influence. The technique proposed by the authors is based on modified ICT and used in previous research: to assess influence of AR/VR/MR/XR as changes of short cognitive/perceptual tests (3 minutes before the work and afterwards) with registration of physiological indices informative in our research.